2018
DOI: 10.1029/2018wr022657
|View full text |Cite
|
Sign up to set email alerts
|

Real‐Time Control of Urban Headwater Catchments Through Linear Feedback: Performance, Analysis, and Site Selection

Abstract: The real‐time control of urban watersheds is now being enabled by a new generation of “smart” and connected technologies. By retrofitting stormwater systems with sensors and valves, it becomes possible to adapt entire watersheds dynamically to individual storms. A catchment‐scale control algorithm is introduced, which abstracts an urban watershed as a linear integrator delay dynamical system, parameterizes it using physical watershed characteristics, and then controls network flows using a Linear Quadratic Reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
41
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(42 citation statements)
references
References 84 publications
(106 reference statements)
1
41
0
Order By: Relevance
“…There are studies that demonstrate the improved hydraulic and hydrological performance of an urban watershed by actively controlling a series of detention ponds. Wong and Kerkez, (2018) reduced the engineered watershed storage volume up to 50% by actively controlling 4 detention ponds depending on their hydraulics. Mullapudi et al, (2017) showed three ponds and a treatment wetland can be controlled simultaneously to reduce downstream flood risk also getting 46.48% nitrate load reduction.…”
Section: Introduction and Literature Reviewmentioning
confidence: 99%
“…There are studies that demonstrate the improved hydraulic and hydrological performance of an urban watershed by actively controlling a series of detention ponds. Wong and Kerkez, (2018) reduced the engineered watershed storage volume up to 50% by actively controlling 4 detention ponds depending on their hydraulics. Mullapudi et al, (2017) showed three ponds and a treatment wetland can be controlled simultaneously to reduce downstream flood risk also getting 46.48% nitrate load reduction.…”
Section: Introduction and Literature Reviewmentioning
confidence: 99%
“…Prior modeling studies have documented the performance of real-time control strategies in decreasing flooding magnitude and peak water level approximately by 40% to 70% (Sadler et al, 2019;Wong and Kerkez, 2018). However, these studies, on the one hand, ignore the physical dynamics by a linearizing system or manually set-up the control rules based on experts' experience.…”
Section: Discussion and Limitationsmentioning
confidence: 99%
“…RTC can be considered as a dynamic, heuristic, and low-cost technique for three perspectives: optimizing operation strategy, adapting UDSs to changing conditions, and improving eco-system (García et al, 2015). By retrofitting the existing UDSs with smart device such as digital controllers and sensors, instead of renewing pipelines or re-sizing storage facilities, RTC adaptively allows existing UDSs to make full use of capacity to selectively purge retained water before the next storm comes by operating remote-controlled actuators (weirs, gates, valves, and orifices) (Wong and Kerkez, 2018). Although RTC has been applied to UDSs for over 50 years since the 1960s, there are still some gaps calling for participation and efforts (Schütze et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, it provides more precise information on the pollutant load during flood events [79,80]. This real-time flow-rate-sensing technology enables the proper management of water distribution systems during flood events in urban watersheds [81].…”
Section: Water Levelmentioning
confidence: 99%